THE INFLUENCE OF THE MAQASHID SHARIA INDEX AND PROFITABILITY ON THE FINANCIAL PERFORMANCE OF SHARIA BANKING LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2020-2022 - Rasmi; Said, Zainal; Husain, Saddan (Institut Agama Islam Negeri Parepare, 2023)
Sharia banking has the aim of seeking maximum profits to improve the financial performance of sharia banking in Indonesia. If sharia banking can achieve these goals, it can be considered to have good financial performance. The aim of this research is to find out whether there is an influence of the sharia maqashid index and profitability on the financial performance of sharia banking by using sharia banking data listed on the Indonesia Stock Exchange in 2020-2022. The benefit of this research is as a data reference for parties interested in information on the financial performance of Sharia Banks listing on the Indonesian Stock Exchange. This study employs a quantitative method with a descriptive approach. The type of research used is associative research. The data collection technique used in this study is documentation, by collecting financial reports of Islamic banks listed on the Indonesia Stock Exchange from 2020 to 2022. The type of data in this study is secondary data. The data analysis techniques used in this study are the Maqashid Sharia Index ratio, the profitability ratio of Return On Equity (ROE), the financial performance ratio of Quick Ratio (QR), and the data analysis technique uses multiple correlation analysis. The results of this study show that the Maqashid Sharia Index significantly influences the financial performance of Islamic banks listed on the Indonesia Stock Exchange from 2020 to 2022. Profitability, measured by Return On Equity (ROE), also significantly affects the financial performance of Islamic banks listed on the Indonesia Stock Exchange from 2020 to 2022, based on hypothesis testing. Therefore, the Maqashid Sharia Index and profitability, measured by Return On Equity (ROE), significantly impact the financial performance of Islamic banks listed on the Indonesia Stock Exchange from 2020 to 2022, based on hypothesis testing. Research suggestions to Sharia Banking is to further improve its financial performance so that can attract more investors to invest in this research useful in providing insight into significant factors influences financial performance, so it can be used to develop strategies which is more effective and provides relevant information for making decisions better investment in the Sharia Banking sector.